Developing graphical visualization for analyzing student adaptability level in online education / Nur Balqis Mohd Azuddin and Norziana Yahya - Mohd Azuddin, Nur Balqis; Yahya, Norziana (College of Computing, Informatics and Media, UiTM Perlis, 2023)
A method or concept of education or learning known as "e-learning" makes use of information technology at any time or place during the teaching and learning process. Early in 2020, the covid-19 outbreak is spreading and having an impact on the educational field. It has also changed how kids learn. As a result, education has undergone a significant transformation. E-learning, or remote learning through digital platforms, has become increasingly popular. The objectives of this project are to create a dashboard and provide useful information about online learning and preparation for future e-learning courses. Analysing the requirements for data analysis of student adaptability level in online learning are one of the project’s objectives. Then, the project’s objectives also required the project to design and develop an analytical dashboard using Microsoft Power BI. After that, the analytical dashboard will be evaluated. Planning, Analysis, Development, and Implementation are the four steps of the methodology that will be employed in this project. Every activity, technique, and outcome that the project applied to accomplish its objective will be defined during each step.